Stability of p53 homologs. - Tobias Brandt; Joel L Kaar; Alan R Fersht; Dmitry B Veprintsev (PLoS ONE)
Most proteins have not evolved for maximal thermal stability. Some are only marginally stable, as for example, the DNA-binding domains of p53 and its homologs, whose kinetic and thermodynamic stabilities are strongly correlated. Here, we applied high-throughput methods using a real-time PCR thermocycler to study the stability of several full-length orthologs and paralogs of the p53 family of transcription factors, which have diverse functions, ranging from tumour suppression to control of developmental processes. From isothermal denaturation fluorimetry and differential scanning fluorimetry, we found that full-length proteins showed the same correlation between kinetic and thermodynamic stability as their isolated DNA-binding domains. The stabilities of the full-length p53 orthologs were marginal and correlated with the temperature of their organism, paralleling the stability of the isolated DNA-binding domains. Additionally, the paralogs p63 and p73 were significantly more stable and long-lived than p53. The short half-life of p53 orthologs and the greater persistence of the paralogs may be biologically relevant.